Systematics studies of for Shorea spp. in Sarawak. - Mohd Syawal, Lokman (Universiti Malaysia Sarawak (UNIMAS), 2017)
Shorea is one of the genera in family Dipterocarpaceae of tribe Shoreae that is diversely distributed in Borneo. It is locally known as Meranti and about 2/3 of the species in Borneo are endemic to Borneo. Detail descriptions of pollen of genus Shorea were still limited. Hence, a study on comparative morphology and pollen ultra-structure of the four Shorea spp. namely Shorea macrophylla (endemic), Shorea palembanica, Shorea seminis and Shorea hemsleyana (endemic) were conducted. Morphological characteristics of pollen of these four Shorea spp. from four different sections: Pachycarpae, Mutica, Bachyptera and Shorea; were also studied. The pollen of the selected species were observed under Scanning Electon microscope (SEM). There were two distinct pollen grain shapes observed within the selected species which were suboblate and prolate spheroidal classified under tricolpate. The size of the pollen vary within and between the selected species based on P/E ratio, range from 0.9-1.08. The pollen of the selected species showed common exine ornamentation that was microreticulate. It was further grouped into three types of reticulation; fine microreticulate either with or without sculpturing, course and compact exine ornamentation. These information were valuable for additional information and identifications of the four Shorea spp. studied.